2018
DOI: 10.1136/bmjopen-2017-020239
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a WeChat-based life review programme for patients with cancer: protocol for a randomised controlled trial

Abstract: IntroductionPatients with cancer often suffer from considerable distress. Life review is a process of recalling, evaluating and integrating life experiences to alleviate a sense of despair and achieve self-integrity. Empirical data have supported the fact that life review is an effective psychological intervention, but it is not always accessible to patients with cancer. There is little evidence of internet-based life review programmes tailored to patients with cancer. This study aims to develop a WeChat-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The intervention group received the WBLRP plus routine care. The WBLRP consisted of four‐section e‐life review interviews and four life review modules, which has been published (Zhang & Xiao, ). The interviews covered each participant's entire life, including the present (cancer experience), adulthood, childhood and adolescence and a summary of their life.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention group received the WBLRP plus routine care. The WBLRP consisted of four‐section e‐life review interviews and four life review modules, which has been published (Zhang & Xiao, ). The interviews covered each participant's entire life, including the present (cancer experience), adulthood, childhood and adolescence and a summary of their life.…”
Section: The Studymentioning
confidence: 99%
“…However, the telephone‐based life review interviews did not provide the opportunity to observe non‐verbal cues. Recently, our research team developed a WeChat‐based life review programme (WBLRP) for cancer patients, based on Erikson's psychosocial development theory and Reed's self‐transcendence theory (Zhang & Xiao, ). Our programme, which has been validated by a panel of experts and patient advisers, contained four‐section e‐life review interviews, Memory Prompts, Review Extraction, Mind Space and E‐legacy products.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other psychotherapies, a life review may be more acceptable and feasible for cancer patients to do. First, reviewing one's life is a naturally occurring, universal mental process in individuals, such as cancer patients, who are in the last life stage (Zhang & Xiao, ). Second, a successful life review could be facilitated not only by a psychologist, but also by a well‐trained nurse, social worker or even a family caregiver (Chen, Xiao, Yang, & Lan, ).…”
Section: Introductionmentioning
confidence: 99%
“…It allows users to interact asynchronously with each other through text messaging, voice messaging, video conferencing, and other means, as well as obtain information and resources from various WeChat platforms at any time. In 2018, our research team developed a WeChat-based life review program for patients with cancer, consisting of e-life review interviews, memory prompts, review extraction, mind space, and e-legacy products [22]. A preliminary study found that the program was acceptable, feasible, and promising in improving the psychospiritual well-being of patients with cancer [23].…”
Section: Introductionmentioning
confidence: 99%